2011
DOI: 10.1108/00346651111170941
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients intake and health status of HIV/AIDS patients

Abstract: PurposeThere are no adequate records on the nutrition of the people living with HIV/AIDS in Nigeria. This paper aims to rectify this.Design/methodology/approachPurposive sampling technique was used to select 200 PLWHA respondents at the Federal Medical Center Idiaba, Abeokuta. A pre‐tested questionnaire was used to collect information on the subjects’ socio‐demographic characteristics and health status of respondents. A three day 24‐hour recall was used to assess the food intake of the subjects. Adequacy of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…This was lower than a study in China which showed about 59.6 and 54.3 per cent of people living with HIV/AIDS with insufficient energy and protein intake, respectively (Hu et al , 2011). A study in Nigeria similarly found a high proportion of people living with HIV/AIDS with poor records of nutrient intake (Bello et al , 2011). The present study also found most respondents with an inadequate intake of vitamin A (94 per cent) and calcium (95 per cent).…”
Section: Discussionmentioning
confidence: 99%
“…This was lower than a study in China which showed about 59.6 and 54.3 per cent of people living with HIV/AIDS with insufficient energy and protein intake, respectively (Hu et al , 2011). A study in Nigeria similarly found a high proportion of people living with HIV/AIDS with poor records of nutrient intake (Bello et al , 2011). The present study also found most respondents with an inadequate intake of vitamin A (94 per cent) and calcium (95 per cent).…”
Section: Discussionmentioning
confidence: 99%
“…It was on this note, the World Health Organization recommended increased protein and energy food requirements by more than 20 and 10%, respectively, for PLWH (WHO, 2003). The common causes of malnutrition among PLWH have been: poverty, inadequate foods intakes (Bello et al, 2011), malabsorption (associated with damaged gastro intestinal tract), and loss of appetite as a result of mouth ulceration, nutrients and drugs interactions side effects and opportunistic infections (Poles et al, 2001). These factors were known for influencing food preferences among ALHIV.…”
Section: Introductionmentioning
confidence: 99%